2016
DOI: 10.2217/fon-2016-0156
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiotherapy for Early Glottic Cancer: Transition to a New Standard of Care?

Abstract: For decades, the standard of care for radiation treatment of early larynx cancers has been conventional treatment using opposed lateral fields encompassing the larynx and overlying neck structures, including the adjacent carotid arteries. While intensity-modulated radiotherapy (IMRT) has replaced conventional radiotherapy for all other head/neck cancer situations, the use of IMRT to treat early glottic cancers remains controversial. The article reviews the published experience with IMRT for this clinical situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In addition, RA is better than other new techniques in PTV dose and preservation of normal structures [36]. Samuels et al have discussed the transition period to carotid-preserving IMRT techniques and the advantages in early-stage laryngeal carcinomas [15]. However, carotid-preserving treatments must also be carefully considered in terms of local failure of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RA is better than other new techniques in PTV dose and preservation of normal structures [36]. Samuels et al have discussed the transition period to carotid-preserving IMRT techniques and the advantages in early-stage laryngeal carcinomas [15]. However, carotid-preserving treatments must also be carefully considered in terms of local failure of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of new radiotherapy techniques such as carotid-sparing treatments has led to a decrease in nonmalignant deaths and is used more often in the treatment of early-stage laryngeal carcinoma patients [15]. In this study, we evaluated the treatment outcomes and the prognostic factors of patients with early-stage glottic laryngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy has good oncological and functional outcomes; however, prolonged treatment duration (6–7 weeks) and long-term side effects such as xerostomia, mucositis, and skin changes are major drawbacks [3]. Open surgery has also equivalent oncologic outcomes, but need for a tracheostomy, opening of the neck and thyroid cartilage, post-operative pain, risk of subcutaneous emphysema, need for hospitalization, and lower voice quality are the disadvantages of this method [4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment using IMRT is more effective in preserving neighboring structures, thus causing fewer unwanted side effects (NUTTING et al, 2009;SAMUELS, FREEDMAN, ELSAYYAD, 2016). In this study, no significant differences were observed between the type of radiotherapy used and the number of muscle functions lost, since the two types of treatment (IMRT and cobalt therapy)…”
Section: Discussionmentioning
confidence: 55%